Evaluation of a radial immunodiffusion test with polysaccharide B antigen for diagnosis of bovine brucellosis. - Jones, L M (1980)
A radial immunodiffusion (RID) test employing a polysaccharide antigen (poly B) was compared with tests currently used in the diagnosis of bovine brucellosis. Over 1,000 sera from vaccinated and infected cattle, all of which had been examined bacteriologically, were used to determine the sensitivity and specificity of the RID, card, Rivanol, and complement fixation tests. The RID test identified 90% of the cattle that were shedding Brucella in their milk. Although the complement fixation test was more sensitive, it was less specific than the RID test in cattle vaccinated as adults with Brucella abortus strain 19. A sensitive screening test, such as the card test, in combination with the RID test could be used in diagnostic laboratories, or even in the field, with little additional expense or technical expertise. An additional advantage is that the RID could be applied to sera from adult cattle as early as 2 months after vaccination, when postvaccinal agglutinins and complement-fixing antibodies may still be present. The indirect hemolytic test was used with some of the sera and was found to be a very sensitive test which could be useful in areas of low incidence but would not be practical for large-scale testing in adult-vaccinated herds.